The Development of Science in Islam and Its Impact on Islamic Education - Yuniendel, Ratna Kasni; Azhari, Devi Syukri (ITScience (Information Technology and Science), 2024)
Islam has a long history in developing science that began in the 7th century. This development was triggered by the teachings of the Qur'an and Hadith that encouraged the Muslims to demand knowledge and understand the universe. In the golden age of Islam (eighth to fourteenth centuries), centers of science such as Baghdad, Cordoba, and Cairo were the birthplace of many great scientists such as Al-Khwarizmi, Ibn Sina, and Al-Razi. They made significant contributions to a wide range of sciences including mathematics, medicine, astronomy, and philosophy. The influence of the development of science in Islam on Islamic education is enormous. First, education in Islam emphasizes the importance of a balance between religious science and general science. Second, many Islamic educational institutions, such as madrasas and universities, are established to facilitate the teaching of science in a comprehensive manner. Third, the curriculum of Islamic education often includes the study of science and technology, in addition to religious studies, to produce broad-knowing and critical-minded individuals. However, the development of science in Islam also faces challenges, especially in the modern era. These challenges include efforts to maintain the relevance of the Islamic educational curriculum to the development of contemporary science as well as the integration of technology into the learning process. Therefore, Islamic education needs to continue to adapt and innovate in order to remain able to make meaningful contributions to the world of science and remain relevant in the midst of changing times.